Exploring the Dynamics of Social Structuration and Lifelong Learning at Museum Lokananta: A Site of Collective Memory - Eufrasia Kartika Hanindraputri; Mohammad Refi Omar Ar Razy (Faculty of Social Science, Universitas Negeri Malang, 2024)
This study aims to analyze the transformation of Museum Lokananta as a social space that represents the dynamics of cultural structuration, collective memory, and lifelong learning practices. Data analysis within the case study method involves processes of categorization, interpretation, and triangulation from various data sources such as interviews, observations, and documents. The central focus is to uncover in-depth meanings of complex phenomena situated within real-world contexts. The data are thematically analyzed to identify social patterns and the dynamics of the relationship between structure and agency. Validity is reinforced through technique triangulation and verification with key informants. The findings demonstrate that Museum Lokananta is not merely positioned as an institution preserving artifacts, but as a reflective arena where social structures (cultural policies, curatorial systems, digital platforms) interact with agency (visitors, curators, communities) in producing and reproducing cultural meanings. Museum Lokananta has transformed into a site of intergenerational dialogue and dynamic cultural expression. The museum also functions as a non-formal pedagogical space that supports historical literacy and social reflection beyond conventional education systems. Lokananta affirms the museum’s role not only as a heritage institution but also as an active agent in meaning-making and ideological contestation, reinforcing its position in shaping an inclusive, collaborative, and sustainable ecosystem of cultural learning amid social transformation and digital cultural shifts.